In vivo imaging of skeletal muscle in mice highlights muscle defects in a model of myotubular myopathy. Issue 1 (2nd January 2016) - Mercier, Luc; Böhm, Johann; Fekonja, Nina; Allio, Guillaume; Lutz, Yves; Koch, Marc; Goetz, Jacky G.; Laporte, Jocelyn
ABSTRACT: Skeletal muscle structure and function are altered in different myopathies. However, the understanding of the molecular and cellular mechanisms mainly rely on in vitro and ex vivo investigations in mammalian models. In order to monitor in vivo the intracellular structure of the neuromuscular system in its environment under normal and pathological conditions, we set-up and validated non-invasive imaging of ear and leg muscles in mice. This original approach allows simultaneous imaging of different cellular and intracellular structures such as neuromuscular junctions and sarcomeres, reconstruction of the 3D architecture of the neuromuscular system, and video recording of dynamic events such as spontaneous muscle fiber contraction. Second harmonic generation was combined with vital dyes and fluorescent-coupled molecules. Skin pigmentation, although limiting, did not prevent intravital imaging. Using this versatile toolbox on the Mtm1 knockout mouse, a model for myotubular myopathy which is a severe congenital myopathy in human, we identified several hallmarks of the disease such as defects in fiber size and neuromuscular junction shape. Intravital imaging of the neuromuscular system paves the way for the follow-up of disease progression or/and disease amelioration upon therapeutic tests. It has also the potential to reduce the number of animals needed to reach scientific conclusions.